2011
DOI: 10.1093/nar/gkr1108
|View full text |Cite
|
Sign up to set email alerts
|

The PolyA tail length of yeast histone mRNAs varies during the cell cycle and is influenced by Sen1p and Rrp6p

Abstract: Yeast histone mRNAs are polyadenylated, yet factors such as Rrp6p and Trf4p, required for the 3′-end processing of non-polyadenylated RNAs, contribute to the cell cycle regulation of these transcripts. Here, we investigated the role of other known 3′-end processing/transcription termination factors of non-polyadenylated RNA in the biogenesis of histone mRNAs, specifically the Nab3p/Nrd1p/Sen1p complex. We also re-evaluated the polyadenylation status of these mRNAs during the cell cycle. Our analysis reveals th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Polyadenylation of histone read-through transcripts might therefore be a signal to trigger their degradation. In this context, it is interesting that in budding yeast, the TRAMP-exosome complex regulates histone metabolism (35). Moreover, it has recently been shown that polyadenylation induces exosome-mediated decay of promoter upstream transcripts (PROMPTs) to control promoter directionality (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Polyadenylation of histone read-through transcripts might therefore be a signal to trigger their degradation. In this context, it is interesting that in budding yeast, the TRAMP-exosome complex regulates histone metabolism (35). Moreover, it has recently been shown that polyadenylation induces exosome-mediated decay of promoter upstream transcripts (PROMPTs) to control promoter directionality (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the correct dependence of histone transcript concentration on cell volume does not require direct feedback suggests that instead it is an intrinsic property of either transcription rate or mRNA degradation. To test if degradation from the 3'-end by the nuclear exosome is required, we analyzed the cell-volume-dependence of histone transcript concentrations in strains where we deleted RRP6, a component of the nuclear exosome exonuclease 32,33 . As shown in Fig.…”
Section: '-To-5'-degradation By the Nuclear Exosome Is Not Necessarymentioning
confidence: 99%
“…This promiscuity implies that there is plasticity in termination options and that there may be an ongoing competition between termination machineries for elongation complexes. Sen1 has also been observed to act both outside NNS, where it participates in processing or termination events at the end of pre-mRNA transcription units (27, 91), and in the resolution of RNA–DNA hybrids (92, 93). …”
Section: Recruitment Of the Nrd1–nab3–sen1 Complex To Its Targetsmentioning
confidence: 99%